Association between weight-adjusted waist index and cognitive impairment in Chinese older men: a 7-year longitudinal study - Lin, Jie; Shen, Hongchen; Yang, Wenjuan; Zhang, Guojun; Sun, Jie; Shen, Wenqin; Huang, Li; Chen, Huajian (Frontiers in Aging Neuroscience, 2025)
BackgroundObesity, through mechanisms such as insulin resistance and systemic low-grade inflammation, can damage the central nervous system and impair cognitive function. Weight-adjusted waist index (WWI) is a novel measure of obesity that may offer more precise assessments of muscle and fat mass. This study aims to investigate the association between WWI and cognitive function in older Chinese men.MethodsData from the 2011–2018 China Longitudinal Health and Longevity Survey (CLHLS) were used in this study. WWI and cognitive function were examined in both linear and non-linear situations using Kaplan–Meier survival curves, multivariate Cox regression models, and restricted cubic spline (RCS) regression.ResultsThis study included 1,392 older Chinese men aged 65 years and over for whom complete data were available. After controlling for all potential confounding variables, our analysis showed a statistically significant positive association between WWI and cognitive decline. Specifically, for every 1 cm/√kg increase in WWI, the risk of cognitive impairment increased by 17% (HR = 1.17, 95% CI: 1.02–1.35). Using 11.52 cm/√kg as the cutoff point for WWI, we found that High WWI was associated with a 44% increased risk of cognitive impairment compared with Low WWI (HR = 1.44, 95% CI: 1.07–1.96). RCS regression analysis confirmed a linear positive correlation between WWI and cognitive impairment.ConclusionHigher WWI is linked to worse cognitive performance in older Chinese men.